Delivering Zero Carbon Buildings: The Role of Innovative Business Models. (2015) - Zhao, Xiaojing; Pan, Wei
Abstract: Zero carbon building (ZCB) has emerged as an innovative approach to improving building energy performance and reducing building carbon emissions. However, the uptake of the ZCB approach is slow, far from the mainstream practice of building. Previous studies have devoted to analyze the technical feasibility and design issues of ZCB. Some have examined the barriers to the adoption of ZCB practices in the market, social, regulatory and/or financial aspects. However, few have explored the role of business models in the delivery of buildings towards zero carbon. The aim of this paper is thus to examine the effect of business model on ZCB, and to explore innovative business models that can stimulate the uptake of ZCB. The paper first reviews the concepts of ZCB and identifies the challenges to ZCB based on the PESTEL analytical framework. The paper then investigates the conceptual framework of business models for ZCB. Nine key elements of the business model are identified, which include offering, target customer, distribution channel, customer interfaces, resource and core competency, partner network, cost and revenue model. Evidence is collected to substantiate the arguments through case study with one recent ZCB project selected from varied contexts. The results of the case study presented an innovative business model that helps address the challenges to delivering ZCB. The research findings help to demonstrate to practitioners the business potential of ZCB and to guide how innovative business models can help accelerate the uptake of the ZCB approach.